Melilite‐like modulation and temperature‐dependent evolution in the framework structure of K2Sc[Si2O6]F. Issue 2 (1st April 2016) - Hejny, Clivia; Kahlenberg, Volker; Eberhard, Tim; Krüger, Hannes
Abstract : This paper describes the crystal structure of synthetic K2 Sc[Si2 O6 ]F in superspace group P 42 / mnm (α, α, 0)000 s (−α, α, 0)0000 with modulation wavevectorsq1 = 0.2982 (4)(a* + b* ) andq2 = 0.2982 (4)(−a* + b* ). The structure is a mixed octahedral–tetrahedral framework composed of [ScO4 F2 ] octahedra, [Si4 O12 ] rings and K in variable coordination. Abstract : The crystal structure of synthetic K2 Sc[Si2 O6 ]F has been solved and refined as an incommensurately modulated structure in (3 + 2)‐dimensional superspace. This paper describes the tetragonal structure in the superspace group P 42 / mnm (α, α, 0)000 s (−α, α, 0)0000 [ a = 8.9878 (1), c = 8.2694 (2) Å, V = 668.01 (2) Å 3 ] with modulation wavevectorsq1 = 0.2982 (4)(a* + b* ) andq2 = 0.2982 (4)(−a* + b* ). Structure refinement taking into account the modulation of positional and ADP parameters for all atoms from 3074 observed main hkl 00 and satellite reflections hklmn of first order with single, m · n = 0, and mixed, m · n = ±1, indices converged to a final R value of 0.0514. The structure is a mixed octahedral–tetrahedral framework composed of [ScO4 F2 ] octahedra, [Si4 O12 ] rings and K in variable coordination. Due to the modulation the O atoms move into and out of the first coordination sphere of K leading to a minimum of five and a maximum of 10 interatomic K—O distances up to 3.1 Å. Although this feature is comparable to observations in modulated fresnoite and melilite group compounds, these structures differ from K2 Sc[Si2 O6 ]F with respect to their topology. On temperature increase the intensity of the satellite reflections decreases until they disappear just above 443 K. The high‐temperature normal structure, in space group P 42 / mnm, is identical to the room‐temperature average structure of K2 Sc[Si2 O6 ]F.